Aktivitas Komunikasi Organisasi dan Kinerja Pendamping dalam Program Gernas Kakao di Kabupaten Polewali Mandar - Nurul Mukhlishah; Amiruddin Saleh; Dwi Sadono (Institut Pertanian Bogor, 2014)
AbstractGernas programs utilize partners to deliver innovative messages and informations that able to empower thefarmers. However, in the process of mentoring it is not neglecting the competences of the are performance of the partners. One effort which can control the performance of the partners is through communication. Communication serves as a main tool for success or failure organization in conjunction with the enviro nment duty. The objectives of this study is to analyze the correlation of organizational communication with the performance of the partners. This research was conducted at Polewali Mandar using survey method. The number of respondents were 33 people based on census method and using correlational analysis to process the results. Results of the study that the frequency of organizational communication significantly correlated to quality of work, a good cooperation of the partners, and knowledge about job, and the level of use a communication channels significantly correlated to quality and quantity of work, a good cooperation of the partners, and knowledge about job.Key words: Organizational communication, performance, program’s partner